Synthesis of Alumina Nanofibers and Composites - Mohd Ridzuan, Nordin; Yong, Liew Kong (InTech, 2010)
Alumina, Al2O3, is a ceramic metal oxide of great importance as building material, refractory material, electrical and heat insulator, attributed to its high strength, corrosion resistance, chemical stability, low thermal conductivity, and good electrical insulation. One phase of alumina, the DŽ-phase is widely used as catalyst, catalyst support and adsorbent because its high porosity and surface area.